The unresolved question : the Anglo-Irish settlement and its undoing, 1912-72 - MANSERGH, NICHOLAS (YALE UNIV Press, 1991)
By the outbreak of World War I, civil war in Ireland was an immediate danger, for the Protestants in Northern Ireland were afraid that Home Rule would place them under the dominion of the Catholic majority in the south. The Anglo-Irish settlement of 1920-25 partitioned Ireland into the Irish Free State (later called the Republic of Ireland) and Ulster, or Northern Ireland. However widespread violence on both sides of the border between those who favored the partition and those who opposed it led to the eventual dissolution of the settlement. This book is a history of Anglo-Irish relations from the time of the settlement until its demise in 1972. Nicholas Mansergh discusses the interplay of concepts, interests, and personalities that shaped the settlement, the purposes it was intended to serve, the measure of its success and failure, and the circumstances of its undoing--in particular the Irish Republic's secession from the Commonwealth in 1949 and the British governments dismantling of the local parliamentary institutions in Northern Ireland in 1972. Mansergh's account of the events of this tumultuous era is unparalleled. As an eminent historian of Ireland who was also an observer of the Irish Revolution and an acquaintance of many of the policy makers and political leaders from mid-century onward, he has been able to provide a major interpretation and synthesis of a period of great importance to Ireland and to Britain.